Injury risk and a tackle ban in youth Rugby Union: reviewing the evidence and searching for targeted, effective interventions. A critical review. Issue 15 (20th June 2016) - Tucker, Ross; Raftery, Martin; Verhagen, Evert
Abstract : It has recently been proposed that the tackle, an integral part of Rugby Union, be banned in school rugby, as a means to reduce the risk of injury. This proposal held that harmful contact should be removed in response to what was termed an unacceptably high-injury risk. Such a ban would represent a significant intervention that could change the nature of Rugby Union. As such, the basis and rationale for such a ban is worthy of critical evaluation. This review aims to describe the research on which such a ban is proposed. It does so through an assessment (identification), estimation (understanding of the magnitude and occurrence) and evaluation (determining acceptability) of the risk before decisions can be made about implementing any risk mitigation strategies. The body of literature describing injury risk, particularly among youths, is indeed thin and fraught with methodological differences that makes definitive conclusions impossible. We describe these, and their implications, arguing that the complete ban on the tackle may be unnecessary in young children, in whom injury risk may not be as high as is often argued, but also that it may have detrimental consequences. Finally, we propose alternative strategies and research questions which must be pursued to effectively reduce risk without creating unintended consequences or changing the nature of the sport.